2014
DOI: 10.1111/2047-3095.12043
|View full text |Cite
|
Sign up to set email alerts
|

Do Problem‐Solving Skills Affect Success in Nursing Process Applications? An Application Among Turkish Nursing Students

Abstract: Students were suggested to use critical thinking, practical approaches, and care plans, as well as revising nursing processes in order to improve their problem-solving skills and nursing process application skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…21,22,29 As Burns et al stated, students acquisition of PS is impeded by many factors such as the lack of opportunities to practice PS skills and the challenges instructors face in teaching the skills in realistic situations. 18 Number of studies revealed that nursing and midwifery students had difficulty in performing PS activities; 14,15,[19][20][21][22] they cannot grasp PS procedures adequately; they are reluctant to utilize PS skills in clinical practice since they find them difficult, timeconsuming and too theoretical. 19,21 Therefore problem/context-based learning strategies are commonly recommended to improve PS skills of students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22,29 As Burns et al stated, students acquisition of PS is impeded by many factors such as the lack of opportunities to practice PS skills and the challenges instructors face in teaching the skills in realistic situations. 18 Number of studies revealed that nursing and midwifery students had difficulty in performing PS activities; 14,15,[19][20][21][22] they cannot grasp PS procedures adequately; they are reluctant to utilize PS skills in clinical practice since they find them difficult, timeconsuming and too theoretical. 19,21 Therefore problem/context-based learning strategies are commonly recommended to improve PS skills of students.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies revealed that the nursing students have moderate or low levels of PS. [19][20][21][22][23] Based on social cognitive theory, students' beliefs concerning their PS ability may affect their PS performance therefore educators should be aware of the relationship between SE and PS. THE RELATIONSHIP BETWEEN SELF-EFFICACY AND PROBLEM SOLVING SE and PS are the main concepts of nursing and midwifery education.…”
Section: Problem Solvingmentioning
confidence: 99%
“…Institutions providing nursing education must raise the PS skills of nurses in order to give qualified health systems the best chance to solve the possible or actualized health problems of individual or groups. PS skills are taught through the application of the "nursing process"education as scientific problem-solving (Bayindir & Olgun, 2015;Burns, O'Donnell, & Artman, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, nursing students were not aware that they had received problemsolving training integrated into the nursing process (Ancel et al, 2015). Moreover, the study by Bayindir and Olgun (2015), which is the only study conducted in Turkey, examined the relationship between PS and the nursing process application skills of nurses and found no correlation between them. However, the nursing process education in Turkey based on PS skills starts from the second term of the four-year undergraduate education and continues for 7 semesters.…”
Section: Introductionmentioning
confidence: 99%
“…4 Akut miyokard infarktüsü (AMİ), koroner arterde ani oluşan vazospazm sonucu miyokarda kan akımının kesilmesi ile miyokardın oksijen gereksiniminde artma olarak tanımlanan küresel bir halk sağlığı problemidir. 4,5 AMİ'nin risk faktörleri arasında; ailede KAH öyküsü, cinsiyet, yaş, yüksek kolesterol, hipertansiyon, diabetes mellitus varlığının yanı sıra sağlıksız beslenme, yetersiz fiziksel aktivite, tütün ve alkol kullanımı gibi davranışsal risk faktörleri de yer almaktadır. 4,[6][7][8] AMİ'nin belirtileri boyuna, çeneye, sol omuza ve kola yayılım gösteren şiddetli ezici, sıkıştırıcı, batıcı ağrının yanı sıra bulantı, kusma, terleme, taşikardi, baş dönmesi, solunum sıkıntısının eşlik etmesidir.…”
unclassified